2015
DOI: 10.1016/j.trci.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Two randomized controlled trials of SB742457 in mild‐to‐moderate Alzheimer's disease

Abstract: BackgroundTwo previous studies of SB742457, a 5-hydroxytryptamine (5-HT6) receptor antagonist, suggested the efficacy of improvements in cognition and global outcome in Alzheimer's disease (AD).MethodsTwo randomized, placebo-controlled trials investigated SB742457 15 and 35 mg daily in subjects with mild-to-moderate AD (Mini-Mental Health State Examination [MMSE] 10–26). Study 1 (n = 576) investigated SB742457 and donepezil (5–10 mg daily) as monotherapy for 6 months. Study 2 (n = 684) investigated SB742457 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 33 publications
(45 reference statements)
1
40
0
Order By: Relevance
“…The negative results from the phase 3 MINDSET study run counter to the phase 2 results with intepirdine that had suggested a potential benefit in Alzheimer disease. 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative results from the phase 3 MINDSET study run counter to the phase 2 results with intepirdine that had suggested a potential benefit in Alzheimer disease. 11…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Even though clinical trials did not support 5-HT 6 antagonist monotherapy among patients with Alzheimer disease, 8,9 2 phase 2 trials suggested that administration of 5-HT 6 antagonists added to cholinesterase inhibitor therapy may improve cognition in Alzheimer disease. 10,11 In one of the phase 2 studies, 10 90 mg/d of idalopirdine (30 mg taken 3 times per day) added to a stable dose of donepezil provided significant improvement in cognitive performance relative to donepezil monotherapy among patients with moderate Alzheimer disease dementia. Therefore, 3 randomized clinical trials (STARSHINE [study 1], STARBEAM [study 2], and STARBRIGHT [study 3]) were conducted to assess the efficacy of idalopirdine when added to donepezil or another cholinesterase inhibitor therapy for the treatment of mild to moderate Alzheimer disease.…”
mentioning
confidence: 99%
“…Further, the results of different studies were inconsistent. For instance, one study found a significant change in global function but not cognition [89], while another report failed to find any significant improvements [90,91].…”
Section: -Ht Receptorsmentioning
confidence: 99%
“…The potential for therapeutic use of 5-HT 6 antagonists in the treatment of AD has been investigated in prior clinical trials that have demonstrated mixed results with respect to clinical efficacy. In clinical trials of SB-742457 (now known as intepirdine), administered as monotherapy to individuals with mild to moderate AD, there was no significant benefit of treatment versus placebo on measures of cognition or global impression of change, although some favorable trends were noted [ 8 , 9 ]. In contrast, studies where 5-HT 6 antagonists were added to existing stable regimens of cholinesterase inhibitors have produced more favorable results, with significant effects observed on measures of cognition and activities of daily living [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%